How can the development of e-modules PBL improve students critical thinking skills and independent in biology learning? - Norlince Bahi; Suyitno Aloysius (University of Muhammadiyah Malang, 2025)
Students' critical thinking skills and independent learning in Indonesia are still at a low level. Teaching materials are needed that encourage students to learn independently and improve their critical thinking skills, one of which is a Problem-Based Learning (PBL) e-module. The purpose of this study is to develop a PBL e-module to enhance the critical thinking skills and independent learning abilities of Phase E students. This is a development study using the ADDIE design. The research subjects were media and teaching material experts, subject matter experts, teachers, and Phase E students at Senior High School 1 Depok. Critical thinking skill data were collected using tests (essay questions), while data on feasibility, practicality, and independent learning were collected using non-tests (questionnaires). The research data were analyzed using descriptive quantitative analysis and one-way manova. The results showed that the PBL e-module was feasible and practical as a teaching material. The effectiveness test results showed that the PBL e-module model was effective in simultaneously improving critical thinking skills and learning independence. Based on these results, the PBL e-module can be used as teaching material by teachers to accustom students to practicing essential skills of thinking and learning independence.